Combined effects of pre-cooling and in-play cooling breaks using ice towels and cold drinks during football matches in warm conditions - Schwarz, E.; Duffield, R.; Alanis, A.; Oliveira, C.; Duarte Muñoz, M.; Alanis, M.; Lara, A.; Costa, J.; Freeze, A.; Meyer, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Playing in hot environmental temperatures is a growing concern for sporting and football organisations worldwide. Therefore, to support player health and minimise performance deterioration during football in the heat, strategies, including cooling procedures and breaks in play, have been proposed; however, investigations in field settings remain scarce (Gouttebarge et al., 2023). METHODS: In total, 22 male academy soccer players (age 17 ± 0.8 y) participated in two matches in warm conditions (25.5 ± 2 °C WBGT) and received a cooling intervention (COOL) or a control condition (CON) in a randomised cross-over design. COOL consisted of cold towels (6-9 °C) and cold drinks (5 °C) for 10min of pre-cooling prior to the warmup, 10min before the kick-off, 10min at halftime and for an additional 3min during cooling breaks at 25min into each half. The CON received a placebo drink (17 °C) and no cooling at the same time frames. Core body temperature (Tcore), heart rate (HR), match running performance via gobal positioning system (GPS), sweat loss and fluid intake, rating-of-fatigue (RoF), rating of perceived exertion (RPE), thermal sensation (TS) and perceptions regarding likeability and performance benefits were measured throughout the match-day. RESULTS: Players reached a maximum Tcore of 39.2 ± 0.5 °C in COOL, which did not differ from CON (39.1 °C ± 0.5 °C; p * 0.05). Further, there were no differences between conditions for Tcore, HR, GPS, RoF or RPE (p*0.05), but TS was lower in COOL during respective breaks (p